2023
DOI: 10.1021/acsami.2c23207
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Morphological Evolution during Corrosion of the Ni-20Cr Alloy in Molten Salt Revealed by Multiscale Imaging

Abstract: Understanding the mechanisms leading to the degradation of alloys in molten salts at elevated temperatures is significant for developing several key energy generation and storage technologies, including concentrated solar and next-generation nuclear power plants. Specifically, the fundamental mechanisms of different types of corrosion leading to various morphological evolution characteristics for changing reaction conditions between the molten salt and alloy remain unclear. In this work, the three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The presence of an interconnected pores-ligaments network indicates that bicontinuous dealloying can occur in the Ni20Cr alloy in FLiNaK at 600 °C. One point of note is that the ligament features are similar to the case of molten chloride dealloying [15][16][17][18][19][20]32,33 and liquid metal dealloying, 51 but are significantly coarser relative to the features observed upon dealloying of Cu-Zn, Ag-Au, and Pt-Ni alloys in aqueous solution such as HClO 4 , 22 H 2 NO 3 , 52 and others, 53,54 surmised to be due to the high homologous temperature in the case of molten salts. Given that the potentials of +1.75, +1.90, and +2.10 V K/K+ indicate bicontinuous dealloying, additional electrochemical and morphological characterization was performed, as presented in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The presence of an interconnected pores-ligaments network indicates that bicontinuous dealloying can occur in the Ni20Cr alloy in FLiNaK at 600 °C. One point of note is that the ligament features are similar to the case of molten chloride dealloying [15][16][17][18][19][20]32,33 and liquid metal dealloying, 51 but are significantly coarser relative to the features observed upon dealloying of Cu-Zn, Ag-Au, and Pt-Ni alloys in aqueous solution such as HClO 4 , 22 H 2 NO 3 , 52 and others, 53,54 surmised to be due to the high homologous temperature in the case of molten salts. Given that the potentials of +1.75, +1.90, and +2.10 V K/K+ indicate bicontinuous dealloying, additional electrochemical and morphological characterization was performed, as presented in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…In a collection of investigations led by Chen-Wiegart et al, [16][17][18]32,33 using in-situ synchrotron X-ray nano-tomography, the authors observed the formation of bicontinuous porous structure on Ni20Cr (wt%) microwires and thin foils at both nano and micron scale when statically exposed to molten chlorides (e.g. KCl-MgCl 2 ) between 500 °C and 800 °C.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, by varying the incident X-ray energy around the absorption edge of the target element, TXM can be extended to X-ray absorption fine structure (XAFS) imaging, enabling the spatially resolved analysis of the chemical state and local coordination structure of elements. TXM–XAFS measurements have successfully visualized the reaction distribution and degradation progression during charging and discharging inside a cathode layer and active material particles. However, the cathode, electrolyte, and anode in an LiB system join to cause an electrochemical reaction. Therefore, it is important not only to individually analyze each element but also to analyze the reaction and degradation behavior of each element while simultaneously observing the entire battery.…”
Section: Introductionmentioning
confidence: 99%